Meaning Pedagogy as a Vector for the Development of Vocational Teacher's Self-Efficacy in Integrative Environment - A.A, Ushakov; N.M, Sazhina; Yu.N, Sinitsyn; A.G, Khentonen; O.V., Grebennikov; A.I, Fialko (International Journal of Engineering and Technology, 2018)
The relevance of this work is due to the fact that in the context of globalization of education and integration processes in educational systems, the requirements to teachers' professionalism and their personal traits increase. The main resource for improving the quality of education is teachers motivated for continuous professional development. Value and meaning-wise attitude to teaching profession defines self-efficacy as confidence in their professional and pedagogical actions. The processes of purposeful formation and development of self-efficacy in the integrative environment are the most important instruments to improve teacher's professionalism. In this regard, this paper reveals the essence, content and structural components of self-efficacy, and identifies the mechanisms of its development in the modern integrative environment in terms of meaning pedagogy. The leading approach to the study is the integrative-systematic approach. It considers the development of self-efficacy on the basis of meaning pedagogy in the conditions of integration of educational environments. The pilot study (self-efficacy testing) engaged 122 university teachers under the age of 35 working as a teacher from 3 to 5 years. The paper defines the essence of the teacher's self-efficacy and its relationship with meaning pedagogy. The study identified the following structural components of teacher's self-efficacy in the modern integrative environment: understanding the professional and pedagogical goal, meaning and results of professional and pedagogical activity, control  loci "I" and "professional and pedagogical activity", and meaningfulness of professional and pedagogical activity as a generalized component of self-efficacy. The results of the pilot study showed the tutoring support for the development of vocational teachers' self-efficacy is necessary. The paper presents the technology of developing teacher's self-efficacy in integrative environment. This technology is based on the tracing individual development as the routes to the future, points of bifurcation. One of the possible directions is selected while passing these points. The research results define new vectors of self-efficacy development based on life-purpose guidelines, significantly expand the theoretical understanding of development and self-development of teachers in the modern integrative educational macro-environment. The paper is interesting for organizing the tutoring support for the development of vocational teachers' self-efficacy. It can also be used in the system of continuous education.